Kualitas Assurance Statement atas Laporan Keberlanjutan - Cindy Vinella; Jason Wibisono; Maria Ellita Ovina; Maya Rianti; Carmel Meiden (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the quality of the assurance statement contained in the sustainability report. This research method uses content analysis method. There are 38 assurance statements from 10 companies included in LQ45 which are the object of research. According to AA1000AS, there are 14 minimum items that must be included in the assurance statement. Of the 38 assurance statements, the researcher classified them based on the name of the company, business sector, name of the assurance provider, and the standard used. The results showed that the compliance level of the 38 assurance statements from 10 companies included in the LQ45 was at a moderate level, namely around 33% - 67%. Keywords: Assurance Statement, Sustainability Report